Endocarditis caused by Stenotrophomonas maltophilia—A rare presentation of an emerging opportunistic pathogen. (2019) - Kogler, William; Davison, Nancy; Richardson, Aaron; Rollini, Fabiana; Isache, Carmen
Abstract: First isolated in 1943, Stenotrophomonas maltophilia ( S. maltophilia ) has historically been of little significance as it was considered a pathogen of low virulence noted to rarely infect immunocompromised hosts. However, over the last 30 years the prevalence of infection caused by the organism has increased significantly. Bacterial endocarditis from S. maltophilia remains exceedingly rare with only a small number of reported cases in the literature. This case involves a 27 year old male with sickle cell anemia with an indwelling right subclavian port who presented to the emergency department with myalgias, fever, and chills. His initial blood cultures grew Gram negative rods later identified as S. maltophilia . Transthoracic echocardiogram showed a mass in the right atrium. Transesophageal echocardiogram revealed a large C-shaped mass with attachment to the tricuspid annulus, mitral valve wall, and port tip in right atrium. The patient underwent sternotomy with removal of the vegetation to prevent embolization. He was treated with intravenous ciprofloxacin and oral trimethoprim/sulfamethoxazole to complete a full 6 weeks of therapy, making a full recovery. This report will further explore the unique presentation of this pathogen along with its epidemiology, resistance mechanisms, risk factors for infection, diagnosis, and appropriate antimicrobial treatment.